Sister chromatid cohesion: simple concept, complex reality - Koshland, Douglas (Henry Stewart Talks, 2009)
Sister chromatid cohesion: simple concept complex reality, Overview of higher order chromosome structure, Smc (structural maintenance of chromosomes) complexes as mediators of higher order chromosome structure, Introduction to cohesin, the Smc complex that mediates sister chromatid cohesion, Biological function of cohesion, Cohesin binding to chromatin, Establishment, maintenance and dissolution of cohesion, The molecular basis of cohesins as chromatid tethers